Mucormycosis and COVID-19 pandemic: Clinical and diagnostic approach - Asim Azhar; Wajihul Hasan Khan; Parvez Anwar Khan; Khaled Alhosaini; Mohammad Owais; Aijaz Ahmad (Elsevier, 2022)
The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is yet to be controlled worldwide, especially in India. The second wave of coronavirus disease 2019 (COVID-19) led to panic and confusion in India, owing to the overwhelming number of the population that fell prey to this highly infectious virus of recent times. In the second wave of COVID-19, the patients had to fight both the virus and opportunistic infections triggered by fungi and bacteria. Repeated use of steroids, antibiotics, and oxygen masks during the management of severely and critically ill COVID-19 patients nurtured opportunistic infections such as mucormycosis. Despite mucormycosis being a decades-old disease, it has gained notice of its widespread occurrence in COVID-19 patients throughout India. Instances of mucormycosis are usually unearthed in immunocompromised individuals and are caused by the inhalation of filamentous fungi, either from the natural environment or through supportive care units. In the recent outbreak during the second wave of COVID-19 in India, it has been seen to cause secondary infection as it grows along with the treatment of COVID-19. Furthermore, COVID-19 patients with comorbidities such as diabetes were more likely to have the mucormycosis co-infection because of their challenged immune systems' inability to fight it.Despite the hype, mucormycosis still remains neglected and least studied, which is predominantly due to all focus on diagnostics, vaccine, and therapeutic research. In this review, we emphasize mainly on the association of mucormycosis in COVID-19 patients. We also present the molecular mechanism of mucormycosis for a better understanding of the fungal infections in patients who have recently been infected with SARS-CoV-2. Better understanding of fungal pathogens, immediate diagnosis, and management of the infections are crucial in COVID-19 patients, as high mortalities have been recorded in co-infected patients despite recovery from COVID-19.